Smart distribution network device for microgrid applications - So, Ping Lam (2013)
This paper focuses on the design of a smart distribution network device for improving the power quality and reliability of the overall power distribution system that the microgrid is connected to. The control design employs a newly developed Model Predictive Control algorithm which optimizes the steady-state and the transient control problems separately to achieve a faster computational time for large power systems. Kalman filters are also employed as state observers to identify the required signals needed for monitoring purposes as well as to extract the harmonic spectra of the grid voltage and the load currents. The design concept is verified through different test case scenarios to demonstrate the capability of the proposed device and the results obtained are discussed.